Analisis Pengaruh Motivasi Kerja dan Pengalaman Kerja terhadap Kinerja Pegawai pada PT. PLN (Persero) Unit Pelaksana Pelayanan Pelanggan (UP3) Ciracas - Muhammad Halim Zulmy Adinanda; Aswin Naldi Sahim; Irawan R. D Budianto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Employee performance is a critical factor in achieving organizational effectiveness, particularly in public service institutions. In practice, variations in employee performance are often associated with differences in work motivation and work experience. This study aims to examine both the partial and simultaneous effects of work motivation and work experience on employee performance at PT Perusahaan Listrik Negara (Persero) Customer Service Implementation Unit (UP3) Ciracas. The research employed a quantitative approach with descriptive and associative methods. A saturated sampling technique was applied, involving all 55 employees as respondents. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS software. The results show that work motivation has a positive and significant effect on employee performance, indicating that higher motivation contributes to better work outcomes. Work experience also demonstrates a positive and significant influence on employee performance, reflecting the importance of accumulated skills and knowledge in improving job effectiveness. Simultaneously, work motivation and work experience significantly affect employee performance, with a strong coefficient of determination, indicating that both variables jointly explain a substantial proportion of performance variation. These findings highlight the importance of strengthening motivational programs and optimizing employee experience to enhance organizational performance.